The Effect of Content Credibility and Attractiveness on Purchase Intention: A Systematic Literature Review - Nisrina Hasna Safardianti; Ratih Hasanah Sudradjat (Bulletin of Community Engagement, 2025)
Marketing strategies through digital influencers have become a key pillar in influencing purchase intention on social media. This study revealed that source credibility, including expertise, trustworthiness, and physical attractiveness, is a key determinant of message effectiveness. Key findings indicate that consumer engagement plays a moderating role in the persuasion process. Highly engaged consumers tend to use the central route (in-depth argument evaluation), while those with low engagement rely more on peripheral cues such as visual aesthetics. This paper aims to identify the credibility and attractiveness of influencers in significantly increasing purchase intention. A major challenge remains, namely ad avoidance. The method used was a Systematic Literature Review (SLR) in accordance with the PRISMA 2020 guidelines. Searches were conducted in Scopus, SINTA, and Google Scholar databases for open-access journal articles published between 2020 and 2025. The results show that consumer behavior is significantly influenced by the level of distraction and relevance of the content presented. Overall, content success depends heavily on the influencer's ability to align credible content with audience needs.